Near‐wall velocities of particles suspended in shear flow and a streamwise electric field - Yee, Andrew J.; Yoda, Minami (Electrophoresis, 2022)
Particles with a diameter of ∼0.5 µm in a dilute (volume fractions φ∞ < 4 × 10−3) suspension assemble into highly elongated structures called “bands” under certain conditions in combined Poiseuille and electroosmotic flows in opposite directions through microchannels at particle‐based Reynolds numbers Rep < < 1. The particles are first concentrated near, then form “bands” within ∼6 µm of, the channel wall. The experiments described here examine the near‐wall dynamics of individual “tracer” particles during the initial concentration, or accumulation, of particles, and the steady‐state stage when the particles have formed relatively stable bands at different near‐wall shear rates and electric field magnitudes. Surprisingly, the near‐wall upstream particle velocities are found to be consistently greater in magnitude than the expected values based on the particles being convected by the superposition of both flows and subject to electrophoresis, which is in the same direction as the Poiseuille flow. However, the particle velocities scale linearly with the change in electric field magnitude, suggesting that the particle dynamics are dominated by linear electrokinetic phenomena. If this discrepancy with theory is only due to changes in particle electrophoresis, electrophoresis is significantly reduced to values as small as 20%–50% of the Smoluchowski relation, or well below previous model predictions, even for high particle potentials.